Analisis Kinerja Keuangan pada Primer Koperasi Pegawai Universitas Pembangunan Nasional â€œVeteranâ€ Yogyakarta - Sulasih, Sulasih (Mabsya: Jurnal Manajemen Bisnis Syariah, 2019)
The purpose of this study is to find out and analyze the extent to which the financial performance conditions that have been achieved by cooperatives in the past 5 years on the basis of assessing business capital turnover, profit margins, economic profitability, own capital profitability are good and to apply and compare knowledge obtained under the real circumstances. This type of research is to describe and solve a problem raised in the study, namely the analysis of financial performance, the research used is a case study with quantitative descriptive analysis, namely the method of data analysis using quantitative calculations (numerical data) used on data of objects that have been collected. The results of this study indicate that judging from the level of business capital turnover has fluctuating movements, when viewed from the profit margin it tends to increase, whereas when viewed from economic profitability tends to decrease and when viewed from the profitability of its own capital tends to increase assessed more able to manage businesses with their own capital.